Phenothiazine-functionalized rGO for electrochemical capacitor - Chong, Kwok Feng; S. P., Lee; N. H. M., Saufi; E. Y. L., Teo (Universiti Malaysia Pahang Publishing, 2023)
The functionalization arose as a technique to improve the physicochemical properties of the reduced graphene oxide (rGO) and consequently enhance the supercapacitor performance. The functionalization compound, phenothiazine (PTZ) introduces nitrogen and sulfur heteroatoms into rGO via the one-pot hydrothermal method at different mass ratio produced PTZ-rGO 5 and PTZ-rGO 10. Incorporation of PTZ on the rGO sheets in PTZ-rGO 5 contributes to the high surface area (163.49 m2 g−1) and pore volume (0.3187 cm3 g−1) properties. Contradictory, overloaded PTZ not only shows a lower reduction effect but also reduces the amount of PTZ functionalized in the PTZ-rGO 10 and consequently shows lower electrochemical performance. The excellent properties enable PTZ-rGO 5 enable it to achieve 119.5 F g−1 at 0.5 A g−1 for its specific capacitance and drive it to be the promising electrode material for supercapacitors.